Inscription territoriale du développement durable et responsabilité environnementale. Ecolabels et Quotas individuels transférables - François Mancebo (VertigO)
Application of sustainable development arouses an argument opposing a utilitarian standpoint and a conservationist standpoint. The opposition is obvious when considering decisions that affects preexistent socio-spatial structures. Therefore, understanding the territorial embedment of sustainable development is a complex yet crucial issue which address organizations and firms environmental responsibility. This article is an attempt to encompass this question through two cases: ecolabelling and Trawl Individual Quotas (TIQs).